2018
DOI: 10.1029/2018gl078316
|View full text |Cite
|
Sign up to set email alerts
|

Bilinearity in the Gutenberg‐Richter Relation Based on ML for Magnitudes Above and Below 2, From Systematic Magnitude Assessments in Parkfield (California)

Abstract: Several studies have shown that local magnitude, ML, and moment magnitude, M, scale differently for small earthquakes (M < ~2) than for moderate to large earthquakes. Consequently, frequency‐magnitude relations based on one or the other magnitude type cannot obey a power law with a single exponent over the entire magnitude range. Since this has serious consequences for seismic hazard assessments, it is important to establish for which magnitude type the assumption of a constant exponent is valid and for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…This is in excellent agreement with other theoretical and empirical studies of M L - M relationships for small events, both in Australia and in abroad (e.g. Allen et al, 2011; Deichmann, 2017; Dost et al, 2018; Edwards et al, 2010, 2015; Munafò et al, 2016; Staudenmaier et al, 2018). Together, the M L corrections and the subsequent conversions to M approximately reduce the number of earthquakes exceeding magnitude 4.5 and 5.0, respectively, by 50% or more (Figure 6).…”
Section: Rationale For Changes To Mean Hazardsupporting
confidence: 91%
“…This is in excellent agreement with other theoretical and empirical studies of M L - M relationships for small events, both in Australia and in abroad (e.g. Allen et al, 2011; Deichmann, 2017; Dost et al, 2018; Edwards et al, 2010, 2015; Munafò et al, 2016; Staudenmaier et al, 2018). Together, the M L corrections and the subsequent conversions to M approximately reduce the number of earthquakes exceeding magnitude 4.5 and 5.0, respectively, by 50% or more (Figure 6).…”
Section: Rationale For Changes To Mean Hazardsupporting
confidence: 91%
“…For example, it is known that the b value is a crucial parameter for seismic hazard assessment (Cornell 1968;Weichert 1980); it represents the relative number of large and small earthquakes in a specific area, and together with the a value, it is useful to provide an estimate of the maximum expected magnitude. However, it has been found that seismic hazard assessments based on M L of small earthquakes likely overestimate the occurrence probability of large earthquakes (Staudenmaier et al 2018). Another application is the discrimination between induced and natural seismicity, where b value deviations from its theoretical value may be symptomatic of induced seismicity (e.g., Stabile et al 2014;Goebel et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, M W is preferred to M L in the probabilistic seismic hazard assessments, both for natural and induced earthquakes. Indeed, unlike M L , M W is not affected by saturation, anelastic attenuation, or scattering problems, and therefore, the fault to rupture provides more reliable estimations of the Gutenberg-Richter parameters (a and b values) (Edwards 2015;Staudenmaier et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…S14b). An additional explanation for the apparent under-representation of low magnitudes (which does not preclude the previous ones) is the scaling break of the (amplitude-based) local magnitude L , which, as shown by several studies [e. g., Bakun 1984;Hanks and Boore 1984;Ben-Zion and Zhu 2002;Edwards et al 2010;Zollo et al 2014;Staudenmaier et al 2018;Lanzoni et al 2019], scales differently with w below 2−4 (with L ∝ 1.5 w ) due to the attenuation of the higher frequency content in the medium (i. e., their corner frequencies remain constant) [Bethmann et al 2011;Munafò et al 2016;Deichmann 2017]. Anti-aliasing in the digital sampling process (an additional low-pass filter) can contribute to the scaling break [Uchide and Imanishi 2018].…”
Section: The Different Kinds Of Mfd Inconsistency and Their Originmentioning
confidence: 94%